Pengaruh Tekanan Kempa, Jenis Kombinasi dan Interaksinya Terhadap Sifat Fisika dan Mekanika Papan Laminasi Kombinasi Kayu dan Non Kayu: Effect Of Felt Pressure, Type of Combination and Their Interaction on The Physical and Mechanical Properties of Wood and Non-Wood Combination Laminated Boards - Raehanayati, Raehanayati; Wulandari, Febriana Tri (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
Lamination technology by making laminated boards is a form of increasing the variety of wood products and an effort to overcome the lack of supply of high-quality wood. Laminate board is a form of artificial board made from laminae that are glued together with the help of compression. The characteristics of laminated board are influenced by several factors, including the type of raw material and compression pressure. The aim of this research is to analyze the effect of variations in compression pressure, types of combination and their interactions on the physical and mechanical properties of laminated board products made from a combination of wood and non-wood. The characteristics of laminated board are influenced by several factors, including the type of raw material and felt pressure. Density test results show that the density value has no significant effect on felt pressure, the combination of types and their interactions. Water content testing shows that the type of combination and compression pressure have a significant effect but the interaction has no real effect. The thickness expansion test shows that the compression pressure has a real effect but the type of combination has no real effect. Thickness shrinkage shows that the type of combination has a real effect but compression pressure and interaction do not have a real effect. MoE testing shows that the type of combination has a real effect but the compression pressure and its interaction do not have a real effect. MoR testing shows that the type of combination has a real effect but the compression pressure and its interaction do not have a real effect. There was an increase in the strength class value after combining wood with non-wood from strength class IV to strength class III. All physics test results have met the standards for laminated boards but the mechanics tests have not met the standards